PENGEMBANGAN BASIS DATA KECELAKAAN LALU-LINTAS - Hikmat Iskandar (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Traffic accident is an unexpected occurrence, scarry, and very costly, but difficult to avoid, it freightens all of the travelers. Traffic Police reported that there was at least 10,000 fatalities occurred in general roads throughout Indonesia, a huge number of wested potential. This is the reason to formulate effort for reducing and preventing accident in the future. This paper aims to discuss the need for developing data base and its effor for handling traffic accident. Background for basic information of accidents, development of database, and tool to execute data base are discussed. The traffic accident recording form as a product of the previous studies are presented as to disseminate to the stake holders and to gain critics and advices.